2021
DOI: 10.3390/antibiotics10080961
|View full text |Cite
|
Sign up to set email alerts
|

The Antimicrobial Properties of Nanotitania Extract and Its Role in Inhibiting the Growth of Klebsiella pneumonia and Haemophilus influenza

Abstract: Titanium dioxide (TiO2) is an antimicrobial agent which is considered of potential value in inhibiting the growth of multiple bacteria. Klebsiella pneumonia and Haemophilus influenza are two of the most common respiratory infection pathogens, and are the most. Klebsiella pneumonia causes fatal meningitis, while Haemophilus influenza causes mortality even in younger patients. Both are associated with bacteremia and mortality. The purpose of this study was to test a new antibacterial material, namely nanotitania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…These include fever reduction, enhancing nutrition and cleaning nasal airway and surrounding environment to prevent co-infection bacteria and respiratory failure. Antibiotics are only used in the case of acquisition of bacterial co-infection, such as Streptococcus pneumoniae and Haemophilus influenzae 17 20 .…”
Section: Introductionmentioning
confidence: 99%
“…These include fever reduction, enhancing nutrition and cleaning nasal airway and surrounding environment to prevent co-infection bacteria and respiratory failure. Antibiotics are only used in the case of acquisition of bacterial co-infection, such as Streptococcus pneumoniae and Haemophilus influenzae 17 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that the long-term oral use of foods containing TiO 2 NPs may increase the risk of colorectal cancer [ 7 ]. In vitro studies have shown that TiO 2 NPs have antimicrobial activity and can promote the production of reactive oxygen species [ 22 , 23 ]. Many studies on the gut have found that they can reduce intestinal microbial diversity and short-chain fatty acid production [ 20 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…This eventually causes membrane and DNA damage that culminates in cell death. Cell death via ROS is often more potent [ 27 ]. A higher MIC value observed in Klebsiella pneumoniae can be attributed to the fact that it is one of the most virulent and resistant species of the Klebsiella genus.…”
Section: Resultsmentioning
confidence: 99%
“…The metal ion interacts with the amine and carboxylic groups of proteins and nucleic acids to cause cell death. This is a less potent and slower mechanism, and thus, a larger amount of MNPs are required for cell death [ 27 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%